Transanal Total Mesorectal Excision: Short-term Outcomes of 1283 Cases from a Nationwide Registry in China. Issue 2 (30th December 2020) - Yao, Hongwei; An, Yongbo; Zhang, Hongyu; Ren, Mingyang; Chen, Chien-Chih; Xu, Qing; Wang, Quan; Zhang, Zhongtao; ,
Abstract : BACKGROUND: Transanal total mesorectal excision is a promising surgical procedure for mid to low rectal cancer. OBJECTIVE: This study aimed to determine the short-term outcomes of Chinese patients treated with transanal total mesorectal excision. DESIGN: This was an observational study using data from an online registry system. SETTING: Study participants were recruited from 40 different centers across 15 provinces in China. PATIENTS: Patients with either benign or malignant rectal disease who underwent transanal total mesorectal excision procedure and were registered in the Chinese Transanal Total Mesorectal Excision Registry Collaborative from May 2010 to November 2019 were included. INTERVENTION: Patients underwent transanal total mesorectal excision. MAIN OUTCOME MEASURES: The primary outcomes measured were the postoperative complications and pathological outcomes. RESULTS: In total, 1283 patients, comprising 888 men (69.2%) and 395 women (39.8%) with a median age of 61 (22–92) years and a median BMI of 23.6 (14.5–46.3) kg/m 2, were analyzed. Among 40 participating centers, the average number of registered cases was 32.1±34.7, and 12 centers (30%) registered >40 cases in the registry. Among 849 patients with rectal cancer who underwent laparoscopic-assisted transanal total mesorectal excision, the conversion rate was 0.5% in the abdominal phase and 1.9% in the perineal phase. Three patients reported urethral injury (0.5%). The postoperative complication rate and the anastomotic leakage incidence were 18.4% and 5.8%. The quality of the total mesorectum excision specimens was found to be complete in 81.9% of patients. In addition, the positive circumferential resection margin rate was 2.8%. LIMITATIONS: The primary limitation of this registry study was the high percentage of missing data (10.8% overall), and, for some of the analyzed variables, up to 35% of the data was missing. Postoperative complications were not monitored after discharge, resulting in a lower morbidity rate than the 30-day morbidity rate reported in other studies. CONCLUSIONS: The short-term outcomes of patients who underwent transanal total mesorectal excision procedures in China were acceptable. See Video Abstract at http://links.lww.com/DCR/B414 . EXCISIÓN TOTAL DEL MESORRECTO POR VÍA TRANSANAL: RESULTADOS A CORTO PLAZO DE 1283 CASOS DE UN REGISTRO NACIONAL EN CHINA: ANTECEDENTES: La excisión total del mesorrecto por vía transanal es un procedimiento quirúrgico prometedor para el cáncer de recto medio y bajo. OBJETIVO: Determinar los resultados a corto plazo de los pacientes chinos tratados con escisión mesorrectal total transanal. DISEÑO: Estudio observacional con datos de un sistema de registro en línea. AJUSTE: Los participantes del estudio fueron reclutados en 40 centros diferentes en 15 provincias de China. PACIENTES: Se incluyeron pacientes con enfermedad rectal benigna o maligna que se sometieron a una cirugía de excisión total del mesorrecto por vía transanal y que se registraron en el Registro Colaborativo de Excisión Total del Mesorrecto por vía Transanal en China desde mayo de 2010 hasta noviembre de 2019. INTERVENCIÓN: Excisión total delmesorrecto por vía transanal. PRINCIPALES MEDIDAS DE RESULTADO: Complicaciones postoperatorias y resultados patológicos. RESULTADOS: Fueron analizados un total de 1.283 pacientes, que comprendían 888 hombres (69, 2%) y 395 mujeres (39, 8%) con una mediana de edad de 61 (22-92) años y una mediana de índice de masa corporal de 23, 6 (14, 5-46, 3) kg / m2. Entre los 40 centros participantes, el promedio de casos registrados fue de 32, 1 ± 34, 7, y 12 centros (30%) inscribieron > 40 casos en el registro. Entre 849 pacientes con cáncer de recto que se sometieron a excisión total del mesorrecto pééor vía transanal asistida por laparoscopia, la tasa de conversión fue del 0, 5% en la fase abdominal y del 1, 9% en la fase perineal. Tres pacientes refirieron una lesión uretral (0, 5%). La tasa de complicaciones posoperatorias y la incidencia de fuga anastomótica fueron del 18, 4% y el 5, 8%, respectivamente. La calidad de las muestras de excisión total del mesorrecto se evaluó como completa en el 81, 9% de los pacientes. Además, la tasa de margen de resección circunferencial positiva fue del 2, 8%. LIMITACIONES: La principal limitación del presente estudio de registros fue el alto porcentaje de datos faltantes (10, 8% en general), y para algunas de las variables analizadas, faltaba hasta el 35% de los datos. Las complicaciones postoperatorias no fueron verificadas después del alta, lo que resultó en una tasa de morbilidad más baja que la tasa de morbilidad a 30 días informada en otros estudios. CONCLUSIONES: Los resultados a corto plazo de los pacientes que se sometieron al procedimiento de excisión total del mesorrecto por vía transanal en China fueron aceptables. Consulte Video Resumen en http://links.lww.com/DCR/B414 . (Traducción—Dr. Xavier Delgadillo )